Scoping Review: Faktor dan Dampak Efikasi Diri pada Tenaga Kesehatan - Muhammad Naval; Tutut Chusniyah (Flourishing Journal, 2025)
Self-efficacy is a common problem in nurses, due to high workload, job demands, high working hours, characterized by several factors related to self-efficacy, namely grit, resilience, burnout, organizational support, job satisfaction, behavior, and work experience. The research method used was scoping review, with PRISMA guidelines, and search for research articles from two databases, namely, scopus, and pubmed. Published research articles range from 2015-2025, with the type of scientific journal publication and English language. The results obtained 11 scientific research articles relevant to self-efficacy in health workers, especially those found in nurses in several countries. The results of the analysis found that the dynamics of existing factors are positively correlated with self-efficacy and are important as a nurse's commitment in managing a very high workload. Conversely, low self-efficacy can cause nurses to experience burnout, decreased mental health, unable to manage their work effectively, in order to increase the need for organizational support and social support is a source of increasing self-efficacy, which is included in the verbal persuasion factor given to nurses so as to increase self-efficacy in job completion. AbstrakEfikasi diri merupakan suatu permasalahan yang umum terjadi pada perawat, dikarenakan beban kerja yang tinggi, tuntutan pekerjaan, jam kerja yang tinggi, ditandai dengan beberapa faktor yang berkaitan dengan efikasi diri yaitu grit, resilience, burnout, dukungan organisasi, kepuasan kerja, perilaku, dan pengalaman kerja. Metode penelitian yang digunakan scoping review,dengan panduan PRISMA, serta penelusuran artikel penelitian dari dua database yaitu, scopus dan pubmed. Artikel penelitian yang dipublikasikan rentang tahun 2015- 2025, dengan tipe publikasi jurnal ilmiah dan berbahasa inggris. Hasil penelitian didapatkan 11 artikel penelitian ilmiah yang relevan dengan efikasi diri pada tenaga kesehatan khususnya yang ditemukan pada perawat di beberapa negara. Hasil analisis didapatkan bahwa dinamika faktor yang ada berkorelasi positif dengan efikasi diri dan penting sebagai komitmen perawat dalam mengelola beban kerja yang sangat tinggi. Sebaliknya, efikasi diri yang rendah dapat mengakibatkan perawat mengalami burnout, kesehatan mental yang menurun, tidak mampu dalam mengelola pekerjaannya dengan efektif, agar meningkat diperlukan adanya dukungan organisasi dan dukungan sosial merupakan sumber dalam meningkatkan efikasi diri, yang termasuk kedalam faktor verbal persuasion yang diberikan kepada perawat sehinga meningkatkan efikasi diri dalam penyelesaian pekerjaan.